3D isotropic resolution diffusion‐prepared magnitude‐stabilized bSSFP imaging with high geometric fidelity at 1.5 Tesla. Issue 8 (16th May 2020) - Gao, Yu; Zhou, Ziwu; Han, Fei; Zhong, Xiaodong; Yang, Yingli; Hu, Peng
Abstract : Introduction: MRI has been increasingly used in radiation therapy to facilitate tumor and organ delineation and assess treatment response. Diffusion MRI can provide cellularity information and may enable functional‐based treatment planning and adaptation. However, strong distortion associated with the conventional diffusion‐weighted single‐shot echo‐planar imaging (DW‐ssEPI) sequence is problematic for accurate target delineation. The goal of this work is to propose a 3D diffusion sequence with minimal distortion for radiation therapy applications. Methods: A 3D diffusion‐prepared magnitude‐stabilized balanced steady‐state free precession sequence (DP‐MS‐bSSFP) was developed. A 2D navigator was acquired during the linear catalyzation stage of the bSSFP readout to estimate the phase, which was then used in a plane‐by‐plane low‐rank constrained reconstruction to correct the shot‐to‐shot k‐space inconsistency. A diffusion phantom was scanned to evaluate and compare the geometric reliability and apparent diffusion coefficient (ADC) accuracy with the conventional DW‐ssEPI. Eight landmarks were selected on each slice of the images to calculate the target registration error (TRE), which was used as a surrogate for geometric fidelity. The phantom was scanned under both 0℃ and room temperature. Brain scans were performed on five healthy volunteers. In the first volunteer, protocols of 1, 2, and 4 shots per Kz plane were compared. In vivo geometric fidelity and ADC accuracy were evaluated on the remaining four volunteers using the protocol of four shots per Kz plane. In the geometric fidelity study, 8–10 landmarks were picked on each slice to calculate the TRE. Regions of interest were placed on the white matter, the cerebellum, and the cerebrospinal fluid region to evaluate the ADC agreement between DW‐ssEPI and DP‐MS using the Bland‐Altman plot. All scans were performed at 1.5 mm isotropic resolution to meet the high‐resolution requirement of many radiotherapy applications. Results: The DP‐MS had drastically improved geometric accuracy compared with DW‐ssEPI on the phantom. The mean TRE decreased from 2.09 mm to 0.70 mm. The percentage difference of the ADC values between the two diffusion sequences were less than 5.5% and 7% for the 0℃ and room temperature study, respectively. The DW‐ssEPI had strong distortion and susceptibility‐related artifacts at tissue air boundary, whereas distortion was minimal in DP‐MS images. Overall, the mean/max TRE was over 2 mm/7 mm in the volunteers for DW‐ssEPI, whereas less than 0.8 mm/2 mm for DP‐MS. Good ADC agreement was observed for the white matter, the cerebellum, and the CSF based on the Bland‐Altman plots. Conclusion: A 3D diffusion sequence was developed and validated. It provided high‐resolution diffusion imaging with mean distortion less than 1 mm at 1.5 T, and is a promising imaging technique for treatment planning and adaptive radiotherapy.